Chekhovian response to Anna Karenina and The Death of Ivan Ilyich: analysis of Leo Tolstoy's artistic influence on Anton Chekhov's life and works - Kubra, Khadija Tul (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2024.